Determinants of Accounting-based Performance: Evidence from Bursa Malaysia - Ismail, Rusmawati; Abdullah, Nur Adiana Hiau; Taufil Mohd, Kamarun Nisham (Universiti Utara Malaysia, 2018)
This study aims to examine the determinants of accounting-based performance of 531 non-financial Malaysian listed companies over the period 2004 to 2012.System generalized method of moments reveals that both prior risk-taking behavior and size are found to be important determinants of performance.A significant positive influence of prior risk-taking behavior on performance implies that risk-averse managers are cognitively influenced by their capability in handling risky investments in the past; consequently enhance confidence in their ability to manage profitable investments. The result appears to support the capital asset pricing model implication.Meanwhile, a significant positive size-performance relationship suggests that investors and fund managers should focus on larger companies as they can have better stock performance.